Chlorogenic acid: Potential source of natural drugs for the therapeutics of fibrosis and cancer - Ebuka-Olisaemeka Nwafor (Elsevier, 2022)
Fibrosis and cancer is described by some epidemiological studies as chronic stages of different disease conditions typically characterized by uncontrolled accumulation of extra-cellular matrix (ECM), thereby leading to inflammation of tissues and organ (lungs, heart, liver and kidney) dysfunction. It is highly prevalent, and contributes to increased mortality rate worldwide. Currently, the therapeutical approaches involving selected medications (bemcentinib, pirfenidone and nintedanib) obtained synthetically, and used in clinical practices for fibrosis and cancer management and treatment has shown to be unsatisfactorily, especially during progressive stages of the disease. With regards to finding a more potent, effective, and promising curative for fibrosis and cancer, there is need for continuous experimental studies universally. However, phytochemical constituents’ particularly phenolic compounds [Chlorogenic acid (CGA)] obtained from coffee, and coffee beans have been predominantly utilized in experimental studies, due to its multiple pharmacological properties against various disease forms. Considering its natural source alongside minimal toxicity level, CGA, a major precursor of coffee have gained considerable attention nowadays from researchers worldwide, owing to its wide, efficacious and beneficial action against fibrosis and cancer. Interestingly, the safety of CGA has been proven. Furthermore, numerous experimental studies have also deduced massive remarkable outcomes in the use of CGA clinically, as a potential drug candidate against treatment of fibrosis and cancer. In the course of this review article, we systematically discussed the beneficial contributions of CGA with regards to its source, absorption, metabolism, mechanistic effects, and molecular mechanisms against different fibrosis and cancer categorization, which might be a prospective remedy in the future. Moreover, we also highlighted CGA (in vitro and in vivo analytical studies) defensive effects against various disorders.